Heme Degradation by Heme Oxygenase Protects Mitochondria but Induces ER Stress via Formed Bilirubin - Müllebner, Andrea (Biomolecules, 2015)
Heme oxygenase (HO), in conjunction with biliverdin reductase, degrades heme to carbon monoxide, ferrous iron and bilirubin (BR); the latter is a potent antioxidant. The induced isoform HO-1 has evoked intense research interest, especially because it manifests anti-inflammatory and anti-apoptotic effects relieving acute cell stress. The mechanisms by which HO mediates the described effects are not completely clear. However, the degradation of heme, a strong pro-oxidant, and the generation of BR are considered to play key roles. The aim of this study was to determine the effects of BR on vital functions of hepatocytes focusing on mitochondria and the endoplasmic reticulum (ER). The affinity of BR to proteins is a known challenge for its exact quantification. We consider two major consequences of this affinity, namely possible analytical errors in the determination of HO activity, and biological effects of BR due to direct interaction with protein function. In order to overcome analytical bias we applied a polynomial correction accounting for the loss of BR due to its adsorption to proteins. To identify potential intracellular targets of BR we used an in vitro approach involving hepatocytes and isolated mitochondria. After verification that the hepatocytes possess HO activity at a similar level as liver tissue by using our improved post-extraction spectroscopic assay, we elucidated the effects of increased HO activity and the formed BR on mitochondrial function and the ER stress response. Our data show that BR may compromise cellular metabolism and proliferation via induction of ER stress. ER and mitochondria respond differently to elevated levels of BR and HO-activity. Mitochondria are susceptible to hemin, but active HO protects them against hemin-induced toxicity. BR at slightly elevated levels induces a stress response at the ER, resulting in a decreased proliferative and metabolic activity of hepatocytes. However, the proteins that are targeted by BR still have to be identified.